Evaluation of visual acuity, contrast sensitivity and spherical aberrations in pseudophakic eyes with an intraocular lens - Wilczyński, Michał; Bartela, Joanna; Konarska, Sylwia; Synder, Aleksandra; Omulecki, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Introduction: The use of modern technologies enables constructing and producing perfected intraocular lenses. Recently, aspheric implants have become widely available. Purpose: The purpose of the study was to evaluate functional results, contrast sensitivity in scotopic conditions and spherical aberrations of the optical system of the eye after phacoemulsification with implantation of aspheric intraocular lens. Materials and Methods: The material was gathered prospectively from January until July 2006. The examined group included patients who received aspheric intraocular lenses Adapt AO or AcrySof SN60WF and who previously had received a conventional foldable spherical lens in the fellow eye. The examined group with an intraocular lens Adapt AO consisted of 25 eyes (25 patients) and the examined group with an intraocular lens AcrySof SN60WF consisted of 12 eyes (12 patients). We examined best corrected visual acuity (BCVA) and intraocular pressure. Contrastometry in scotopic conditions and aberrometry were performed. Intraoperative and early postoperative complications were noted. For statistical analysis non-parametric U Mann-Whitney test was used, all calculations were performed for the level of significance α=0.05. Results: In the examined groups there were no intraoperative and early postoperative complications. In both groups, there was no statistically significant difference in mean postoperative BCVA between eyes with an aspheric implant and eyes with a spherical lens. Assuming the mean contrast sensitivity in eyes with spherical implants as 100%, we observed that in eyes with an aspheric lens it was better nearly by one third. Mean value of spherical aberrations with a pupil diameter of 5mm (Zernike RMS 5 mm) in eyes with an aspheric lens was significantly lower in comparison with eyes with a spherical implant (p<0.05). Similarly, mean value of higher order spherical aberrations with a pupil diameter of 5 mm (Higher Order Zernike RMS 5 mm), in eyes with an aspheric lens was significantly lower in comparison with eyes with a spherical implant (p<0.05). Conclusions: Using aspheric lenses Adapt AO and AcrySof SN60WF allows for achieving very good functional and anatomic results and it enables to achieve better contrast sensitivity in scotopic conditions, as well as significantly decreases spherical aberrations of the optical system of the eye, in comparison with conventional spherical lenses.